2011
DOI: 10.3109/00365548.2011.621446
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D supplementation did not prevent influenza-like illness as diagnosed retrospectively by questionnaires in subjects participating in randomized clinical trials

Abstract: Background Vitamin D deficiency has been associated with a number of diseases, including influenza. Whether or not this reflects a causal relationship is unknown. We therefore wanted to examine if supplementation with vitamin D would affect the incidence and severity of influenza-like disease. Methods Questionnaires on influenza were sent to subjects participating in ongoing placebo-controlled intervention studies with vitamin D supplementation, up until the end of April 2010. Results Five hundred and sixt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
37
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(38 citation statements)
references
References 30 publications
0
37
1
Order By: Relevance
“…Of the remaining trials ( Table 4 ), 3 evaluated infection rates and antibiotic use in adults [88-90] and single trials studied populations with: hepatitis C virus (HCV) [91] , heart transplants [92] , HIV [93] , schistosomiasis [94] , and infection in pregnancy [95] . Of these manuscripts, 2 combined multiple randomized, controlled data sets [86, 95] and 8 provided a secondary analysis of previously published data [64, 73, 78, 84, 86, 89, 90, 95] . All studies were double blinded except for 2 that used a single blind model [85, 94] and 6 that were non-blinded [58, 61, 65, 71, 87, 91] .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Of the remaining trials ( Table 4 ), 3 evaluated infection rates and antibiotic use in adults [88-90] and single trials studied populations with: hepatitis C virus (HCV) [91] , heart transplants [92] , HIV [93] , schistosomiasis [94] , and infection in pregnancy [95] . Of these manuscripts, 2 combined multiple randomized, controlled data sets [86, 95] and 8 provided a secondary analysis of previously published data [64, 73, 78, 84, 86, 89, 90, 95] . All studies were double blinded except for 2 that used a single blind model [85, 94] and 6 that were non-blinded [58, 61, 65, 71, 87, 91] .…”
Section: Resultsmentioning
confidence: 99%
“…Two positive studies found fewer RTI [79] and decreased cold and influenza incidences [84] with daily vitamin D 3 doses between 400 IU and 2000 IU for 6 months and 36 months, respectively. However, the remaining trials found no change in the incidence or severity of RTI or influenza symptoms following doses of vitamin D 3 given daily (2,000 IU doses for 4 months [80] or 1,111-6,800 IU doses for 3 months during influenza season [86] ) or monthly (100,000 IU doses for 18 months) [77] .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…11 Moreover, vitamin D-induced antiviral peptides were shown to be effective against the herpes simplex type 1, adenovirus, human immunodeficiency virus, and chickenpox virus as has been implicated in the previous studies. 26 Furthermore, Science et al 27 demonstrated that a higher risk for viral URTIs which was confirmed by polymerase chain reaction (PCR) was associated with low vitamin D levels. The authors revealed that the risk for URTIs increased by 50%, when vitamin D levels were below 70 nmol/L, whereas the risk increased by 70%, when vitamin D levels were below 50 nmol/L.…”
Section: Discussionmentioning
confidence: 99%